Ex Post Efficiency and Individual Rationality in Incentive Compatible Trading Mechanisms - Stefan Lundgren (The Research Institute of Industrial Economics (IUI), 1988)
This paper concerns the design of a trading mechanism for a group of traders when their valuations of the good are private information and they bargain over who shall consume more than his initial endowment and who shall consume less. It is shown that there generally exists a set of initial endowments of the traded commodity such that it is possible to design a trading mechanism which is incentive compatible, individually rational and ex post efficient.
Keywords: O24; 330; Efficient trading; mechanism design.; Verhandlungen; Theorie